Myocardial deformation imaging by 2D speckle tracking echocardiography for assessment of diastolic dysfunction in murine cardiopathology - Daniels, L. J.; Macindoe, C.; Koutsifeli, P.; Annandale, M.; James, S. L.; Watson, L. E.; Coffey, S.; Raaijmakers, A. J. A.; Weeks, K. L.; Bell, J. R.; Janssens, J. V.; Curl, C. L.; et al. (Scientific reports, 2023)
Diastolic dysfunction is increasingly identified as a key, early onset subclinical condition characterizing cardiopathologies of rising prevalence, including diabetic heart disease and heart failure with preserved ejection fraction (HFpEF). Diastolic dysfunction characterization has important prognostic value in management of disease outcomes. Validated tools for in vivo monitoring of diastolic function in rodent models of diabetes are required for progress in pre-clinical cardiology studies. 2D speckle tracking echocardiography has emerged as a powerful tool for evaluating cardiac wall deformation throughout the cardiac cycle. The aim of this study was to examine the applicability of 2D speckle tracking echocardiography for comprehensive global and regional assessment of diastolic function in a pre-clinical murine model of cardio-metabolic disease. Type 2 diabetes (T2D) was induced in C57Bl/6 male mice using a high fat high sugar dietary intervention for 20 weeks. Significant impairment in left ventricle peak diastolic strain rate was evident in longitudinal, radial and circumferential planes in T2D mice. Peak diastolic velocity was similarly impaired in the longitudinal and radial planes. Regional analysis of longitudinal peak diastolic strain rate revealed that the anterior free left ventricular wall is particularly susceptible to T2D-induced diastolic dysfunction. These findings provide a significant advance on characterization of diastolic dysfunction in a pre-clinical mouse model of cardiopathology and offer a comprehensive suite of benchmark values for future pre-clinical cardiology studies.